Variation in HIV-1 Tat and Vpr protein amino acid sequences and its association with vascular health measures in a South African cohort: an exploratory study - Esmé Jansen van Vuren; Yolandi Breet; Adriaan Jacobs; Iolanthé M. Kruger; Monray Edward Williams (Virology Journal)
Abstract Objectives Human immunodeficiency virus (HIV)-1 is associated with adverse cardiovascular-related outcomes. Subtype-specific variations in the amino acid sequences of Tat and Vpr HIV-1 proteins are associated with differential clinical outcomes in people living with HIV (PLHIV). Given the diverse clinical outcomes related to different HIV subtypes, it is crucial to evaluate the variations in the sequence of Tat and Vpr amino acids in geographical regions where subtype C predominates, such as South Africa. This study aimed to determine whether specific Tat and Vpr protein amino acid variants (alone or in combination) are associated with vascular health measures and predict incident hypertension and all-cause mortality over a five-year period. Methods A cohort of n = 60 treatment-naïve PLHIV at baseline and n = 35 at a five-year follow-up was investigated. Standardized vascular health measures, including carotid intima-media thickness (cIMT), cross-sectional wall area (CSWA) and carotid-radial pulse wave velocity (crPWV), as well as Sanger sequencing for Tat/Vpr analysis, were performed. The associations of vascular health measures with Tat and Vpr amino acid variants were investigated. Results We found that the variation in amino acid sequence in Tat only (p = 0.039) and Tat/Vpr (p < 0.001) were associated with crPWV at baseline. Variation in the Tat and Vpr amino acid sequence did not predict incident hypertension in five years or all-cause mortality. Conclusion The variants of the Tat and Vpr amino acid sequence were associated with arterial stiffness, which may be an underlying mechanism for cardiovascular disease development in PLHIV.